Pemberdayaan Perempuan Melalui Home Industri Batik Sekar Jagad di Dusun Tanuraksan Desa Gemeksekti Kabupaten Kebumen - Puput Faiqoh; Liliek Desmawati (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
The purpose of this research is to describe the empowerment process that includes aspects of planning, implementation, evaluation, and supporting factors and inhibitors of women empowerment through the home industry Batik Sekar Jagad in improving the economy family in Tanuraksan hamlet of Gemeksekti village in Kebumen district. The method used in this research is a qualitative approach. Data collection techniques used interview techniques, observations, and documentation. The validity techniques of the data used include the triangulation of the source and method. The results of the research known that 1) the process of empowering women in the home industry Batik Sekar Jagad through the planning stage, implementation, evaluation; 2) supporting factors, among others, the support of Disperindag while the inhibiting factor among other prolonged hot weather and health conditions that began to decline.